Systemic and Intra-Nodal Activation of NK Cells After Rituximab Monotherapy for Follicular Lymphoma - Enqvist, Monika; Jacobs, Benedikt; Junlén, Henna R.; Schaffer, Marie; Melén, Christopher M.; Friberg, Danielle; Wahlin, Björn Engelbrekt; Malmberg, Karl-Johan (Frontiers in Immunology, 2019)
Monotherapy with the anti-CD20 monoclonal antibody rituximab can induce complete responses (CR) in patients with follicular lymphoma (FL). Resting FcRγIII+ (CD16+) natural killer (NK) cells respond strongly to rituximab-coated target cells in vitro. Yet, the contribution of NK cells in the therapeutic effect in vivo remains unknown. Here, we followed the NK cell repertoire dynamics in the lymph node and systemically during rituximab monotherapy in patients with FL. At baseline, NK cells in the tumor lymph node had a naïve phenotype albeit they were more differentiated than NK cells derived from control tonsils as determined by the frequency of CD56dim NK cells and the expression of killer cell immunoglobulin-like receptors (KIR), CD57 and CD16. Rituximab therapy induced a rapid drop in NK cell numbers coinciding with a relative increase in the frequency of Ki67+ NK cells both in the lymph node and peripheral blood. The Ki67+ NK cells had slightly increased expression of CD16, CD57 and higher levels of granzyme A and perforin. The in vivo activation of NK cells was paralleled by a temporary loss of in vitro functionality, primarily manifested as decreased IFNγ production in response to rituximab-coated targets. However, patients with pre-existing NKG2C+ adaptive NK cell subsets showed less Ki67 upregulation and were refractory to the loss of functionality. These data reveal variable imprints of rituximab monotherapy on the NK cell repertoire, which may depend on pre-existing repertoire diversity.